2020
DOI: 10.12968/jowc.2020.29.9.488
|View full text |Cite
|
Sign up to set email alerts
|

Use of bromelain in cutaneous wound healing in streptozocin-induced diabetic rats: an experimental model

Abstract: Objective: To assess the effect of bromelain on different aspects of the wound healing process in type 1 diabetic rats. Method: In this study, 112 streptozocin-diabetic (type 1) male Wistar rats were euthanised; 28 each on days three, five, seven and 15, after a wound incision had been made. To estimate changes in a number of different cellular and tissue elements, histological sections were provided from all wound areas and stained with haematoxylin and eosin. Some 1.056mm2 of total wound area from all specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The results of the in vitro assessment revealed that the bromelain extracted from macambira leaves enabled cell migration similar to that observed in the positive control, i.e., complete healing was achieved within 24 h. A previous study that assessed the in vivo healing activity of the pineapple peel protein extract reported no significant difference in the lesion histology results between the control and treatment groups [107]. Fathi et al (2020) [32] assessed the effect of bromelain on the various aspects of the wound healing process in type-1 diabetic rats. The authors reported that bromelain caused significant wound contraction and also reduced the formation of the granulation tissue by the 7 th day after treatment.…”
Section: Wound Healing Activity In Vitromentioning
confidence: 56%
See 1 more Smart Citation
“…The results of the in vitro assessment revealed that the bromelain extracted from macambira leaves enabled cell migration similar to that observed in the positive control, i.e., complete healing was achieved within 24 h. A previous study that assessed the in vivo healing activity of the pineapple peel protein extract reported no significant difference in the lesion histology results between the control and treatment groups [107]. Fathi et al (2020) [32] assessed the effect of bromelain on the various aspects of the wound healing process in type-1 diabetic rats. The authors reported that bromelain caused significant wound contraction and also reduced the formation of the granulation tissue by the 7 th day after treatment.…”
Section: Wound Healing Activity In Vitromentioning
confidence: 56%
“…Bromelain is also extensively used as an active ingredient in toothwhitening dentifrices and skincare products [29]. Bromelain may also be used for promoting and accelerating wound healing indices and improving the biomechanical parameters of diabetic wounds [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Bromelain, a complex mixture of proteolytic cysteine proteases obtained from stem of pineapple (Ananas comosus) is a food supplement exhibiting a variety of pharmacological activities. Various studies substantiate the bromelain's mucolytic [13], wound healing [14], fibrinolytic [15], antiedematous [16], antithrombotic [17], anti-inflammatory [18], antioxidant [19], anticancer [20] as well as immunomodulatory activity [21]. Bromelain significantly decreases COX-2 and PGE-2 expression and lower the cytokines (IL-1β, IL-6 and TNF-α) secretion from immune cells in inflammatory conditions [22,23].…”
Section: Introductionmentioning
confidence: 94%
“…Their phytochemical content is the purpose of their remedial features in wound repair. Other phytochemicals and plant-derived substances were investigated for their wound-healing activity as flavonols, flavanones, isoflavones, flavanols, flavonolignans, proanthocyanidins (Carvalho et al 2021), β-glucans (Majtan and Jesenak 2018), bromelain (Fathi et al 2020), curcumin (Akbik et al 2014. It was disclosed that different botanicals and medicinal plants are widely used as a topical treatment for wound repairing, such as aloe vera, banana leaves (Sivamani et al 2012), turmeric, Centella asiatica, Rosmarinus officinalis, Calendula officinalis (Artem Ataide et al 2018).…”
Section: Introductionmentioning
confidence: 99%